Pengaruh Capital Adequacy Ratio (CAR), Dana Pihak Ketiga(DPK), Non Performng Finance terhadap Profitabilitas Perbankan Pada Tahun 2016 - 2020 - Farhan Naufal; Mira Kartika Dwi Djunaedi (UNIVERSITAS KALBIS, 2023)
This study aims to determine whether the capital adequacy ratio, non-performing finance, third party funds affect the profitability of Islamic banking. The grand theory in this study uses Agency Theory. The population in this study is Islamic banking registered on the OJK website. Using purposive sampling technique by using secondary data. The results of this study indicate that the capital adequacy ratio has a positive and insignificant effect, third party funds have a negative and insignificant effect on the profitability of Islamic banking and non-performing finance has a negative and significant effect on the profitability of Islamic banking.